MgAl2O4-V2AlC composite material ceramic blade for metallurgical industry and preparation method of MgAl2O4-V2AlC composite material ceramic blade

By adopting MgAl2O4-V2AlC composite material and spiral fan-shaped ceramic blades, the problems of insufficient brittleness, vulnerability and thermal shock resistance in high-temperature environments are solved, and high density, low thermal conductivity, excellent high-temperature strength and wear resistance are achieved, extending service life and improving processing performance.

CN119551979APending Publication Date: 2025-03-04TAIZHOU HONGHUA METALLURGICAL MACHINERY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411456899.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

Existing high-performance structural ceramic materials exhibit brittleness, vulnerability, size and structural limitations, insufficient thermal shock resistance and difficult to regulate the material microstructure in high temperature environments, making it difficult to meet the higher requirements of the metallurgical industry for high-temperature workpieces.

Method used

Using MgAl2O4-V2AlC composite material, ceramic blades with a spiral fan structure were prepared by molding, sintering and CNC lathe processing as raw materials through 75-90% MgAl2O4 powder and 25-10% V2AlC powder and tempering agent (a mixture of magnesium-chromium spinel, Si and polyethylene glycol) as raw materials.

Benefits of technology

It significantly reduces the thermal expansion coefficient of ceramic blades, enhances thermal shock resistance and service life, improves the bonding, high temperature stability, strength, toughness and wear resistance of materials, optimizes processing performance and yield, and is suitable for long-term service in the high-temperature environment of the metallurgical industry.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119551979A_ABST
    Figure CN119551979A_ABST
Patent Text Reader

Abstract

The invention relates to a MgAl2O4-V2AlC composite material ceramic blade for the metallurgical industry and a preparation method of the MgAl2O4-V2AlC composite material ceramic blade, and belongs to the technical field of composite ceramics. The composite material consists of 75 to 90 weight percent of high-purity MgAl2O4 powder and 25 to 10 weight percent of V2AlC powder, and 2 to 10 weight percent of a tempering agent is added. The preparation method comprises the following steps: firstly, mixing a part of the conditioning agent with the MgAl2O4 powder, then sequentially adding the V2AlC powder and the rest of the conditioning agent, and carrying out compression molding and drying after mixing. The green body is subjected to hot isostatic pressing sintering, heat preservation is carried out for 0.5-10 hours at the temperature of 500-900 DEG C, and then heat preservation is carried out for 2-20 hours in the argon atmosphere under the conditions of 1000-1300 DEG C and 10-200 MPa. And after sintering, processing by a numerically controlled lathe to obtain the ceramic blade. By introducing a V2AlC reinforcing phase, the material forms continuous chemical bonding at high temperature and high pressure, and has high strength and fracture toughness. And the metal ceramic characteristic of the V2AlC improves the machining performance, so that the composite material has high density, low heat conductivity and excellent high-temperature strength and wear resistance, and the service life of the composite material is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite ceramics, and in particular relates to a MgAl2O4-V2AlC composite material ceramic blade for metallurgical industry and a preparation method thereof. Background Art

[0002] As the metallurgical industry continues to increase its requirements for material performance under high temperature conditions, traditional heat-resistant alloy steel components are gradually unable to meet the needs of modern industrial production due to their performance limitations in high temperature environments. Existing heat-resistant alloy steel components often face problems such as poor high-temperature creep performance, high thermal conductivity, and short service life, which limits the efficiency and life of metallurgical equipment in actual production processes.

[0003] In order to deal with these problems, research institutions at home and abroad have begun to explore the use of high-temperature ceramics with outstanding characteristics such as good physical and chemical properties, high strength, and excellent high-temperature creep performance to manufacture high-temperature ceramic components to replace existing heat-resistant alloy steel components, which is expected to solve the outstanding problems caused by heat-resistant alloy steel components. At present, domestic and foreign research institutions have studied ceramic blades made of materials such as silicon oxide, silicon carbide, silicon nitride and their composite materials, some of which have been put into practical use, and can improve the problems of high thermal conductivity and poor high-temperature creep performance of heat-resistant steel pads.

[0004] Taking the prior art as an example, CN105777132A discloses a bending-resistant ceramic-based composite material, which improves the bending resistance of ceramic materials by compounding multiple materials such as silicon carbide, silicon nitride, and silicon dioxide. However, the prior art still has some significant defects in the preparation of high-performance structural ceramics: 1. Brittleness and fragility: Existing high-performance structural ceramics are typical hard and brittle structural materials. At the same time, temperature changes have a significant impact on their elastic-plastic and high-temperature creep properties. Their material composition, microstructure design and performance regulation have always been the difficulties and hotspots of their scientific research. Although high-performance structural ceramic materials have high strength and wear resistance, they are very brittle and prone to cracking and damage during use. Especially in complex thermodynamic environments, their elastic-plastic and high-temperature creep properties are often not ideal.

[0005] 2. Size and structure limitations: Existing high-performance ceramic materials face great technical challenges in the preparation of complex structures, large or small-sized parts. Defects are easily generated during the manufacturing process, the yield is low, and the processing accuracy is not high, which makes it difficult for ceramic materials to meet the needs of complex geometric shapes or extreme size parts.

[0006] 3. Insufficient thermal shock resistance: Although ceramic materials have excellent high-temperature strength, their thermal shock resistance is relatively poor. Especially in an environment with rapid temperature changes, the material is prone to thermal shock damage, which affects its service life.

[0007] 4. Difficulty in regulating material microstructure: Existing ceramic materials still face great difficulties in microstructure design and performance regulation. How to improve the density of ceramic materials, reduce their thermal conductivity, and enhance their resistance to high-temperature creep is still a difficult point and research hotspot in the field of materials.

[0008] Therefore, in order to overcome these shortcomings of existing ceramic materials in application, it is urgent to develop a ceramic composite material with lower thermal expansion coefficient, higher strength, excellent wear resistance and thermal shock resistance. At the same time, on the basis of ensuring the excellent performance of the material, it is also necessary to ensure the material's low damage, few defects, high yield and high-precision processing performance to meet the metallurgical industry's higher requirements for high-temperature workpieces. Summary of the invention

[0009] The present invention aims to overcome the defects of the prior art and aims to provide a MgAl2O4-V2AlC composite ceramic blade having the characteristics of high density, low thermal conductivity, excellent high temperature strength, excellent thermal vibration stability and wear resistance, long service life and the like, and a preparation method thereof, in order to address the technical defects existing in the existing heat-resistant steel blades used in the metallurgical industry, thereby limiting the technological progress and economic benefits of the industry.

[0010] To achieve the above object, the technical solution adopted by the present invention is: Step 1, raw material composition: 75-90wt% MgAl2O4 powder and 25-10wt% V2AIC powder are used as raw materials, and 2-10wt% of a conditioning agent is used as an additive; wherein the conditioning agent is a mixture of magnesium chromium spinel, Si and polyethylene glycol in a mass ratio of 1:1:5, the purpose of which is to improve the bonding and high temperature stability of the composite material; Step 2, raw material mixing: the raw materials and additives in step (1) are configured in a percentage ratio, firstly, half of the conditioning agent is added to the MgAl2O4 powder for mixing, so that the conditioning agent covers the surface of the MgAl2O4 raw material; after mixing evenly, V2AlC powder and the remaining conditioning agent are added in sequence, and mixed thoroughly, so that the V2AlC powder can cover the MgAl2O4 powder; Step 3, molding, sintering and processing: molding the raw materials mixed uniformly in step (2), and obtaining a green body after drying; placing the green body material in a hot isostatic pressing sintering furnace, keeping the temperature at 500-900° C. under vacuum conditions for 0.5-10 hours, then raising the temperature to 1000-1300° C. under argon atmosphere, and keeping the temperature at 10-200 MPa hot isostatic pressing conditions for 2-20 hours to obtain a sintered green body, and then machining it on a CNC lathe to obtain a ceramic blade; As a preferred solution, the purity of MgAl2O4 powder is ≥95wt%, and the particle size is less than 3mm; the purity of V2AlC powder is ≥95wt%, and the particle size is less than 200μm; the purity of magnesia-chrome spinel powder is ≥92wt%, and the particle size is less than 50μm; the purity of Si powder is ≥95wt%, and the particle size is less than 10μm; the molding pressure is 50-300MPa, and the pressure is maintained for 5-30min; the purity of argon is ≥99%.

[0011] As a preferred solution, the ceramic blades are in a spiral fan-shaped structure, the spiral angle of the ceramic blades is 15-25°, the ceramic blades are fixedly connected by welding plates, and a spiral columnar structure is formed between the ceramic blades. The ceramic blades adopt a spiral fan-shaped structure with a spiral angle of 15-25°. They are fixedly connected by welding plates to form a spiral columnar structure, which significantly improves their working efficiency and stability under high temperature and high pressure environments. The spiral structure makes the flow of gas or liquid smoother, reduces turbulence and resistance, further optimizes the heat transfer and mass transfer effects, and improves the overall performance of the equipment. In addition, the structure further enhances the mechanical strength and durability of the blades, further reduces the risk of wear and damage of the blades under extreme working conditions, extends the service life, and improves reliability and service efficiency.

[0012] Compared with the prior art, the present invention has the following beneficial technical effects: 1. Reduced thermal expansion coefficient, enhanced thermal shock resistance and service life: The present invention uses MgAl2O4 with a low thermal expansion coefficient as the base material, which effectively reduces the thermal expansion coefficient of the ceramic blade, thereby significantly improving the thermal shock resistance of the composite material and extending its service life under high temperature conditions. This feature overcomes the shortcomings of traditional heat-resistant alloy steel parts with limited performance in high temperature environments.

[0013] 2. Improve the bonding and high temperature stability of the composite material: By introducing a conditioning agent, especially a conditioning agent composed of magnesium chromium spinel, Si and polyethylene glycol in a mass ratio of 1:1:5, the bonding and high temperature stability of the composite material have been greatly improved. This conditioning agent not only improves the bonding performance of the material, but also enhances the high temperature oxidation resistance of the material.

[0014] 3. Improve the strength, toughness and high temperature resistance of the composite material: V2AlC, as a reinforcing phase, forms a high-strength and high-toughness bonding phase network with the MgAl2O4 matrix material by virtue of its excellent yield strength, high melting point and high temperature stability. Compared with traditional ceramics, the composite material of the present invention exhibits better flexural strength, fracture toughness and high temperature resistance.

[0015] 4. Optimize processing performance and yield rate: Due to the self-lubricity and cubic isotropy of V2AlC, the material's machining performance on CNC lathes is significantly improved, the composite material has higher processing accuracy, less damage, fewer defects, and improved yield rate. This feature enables the material to perform well in the processing of complex structures and extreme size parts, overcoming the technical difficulties of traditional ceramics in precision processing.

[0016] 5. Significantly enhanced wear resistance and thermal shock resistance: The composite material of the present invention not only has excellent high-temperature strength and wear resistance through the combination of V2AlC and MgAl2O4, but also maintains excellent thermal shock resistance under frequent thermodynamic fluctuations. This makes the material particularly suitable for long-term service in high-temperature environments in the metallurgical industry, significantly improving the working efficiency and economic benefits of the equipment.

[0017] In summary, the MgAl2O4-V2AlC composite ceramic blade of the present invention has achieved significant improvements in thermal expansion coefficient, material strength, toughness, high temperature resistance, wear resistance and processing performance, effectively overcoming the shortcomings of the prior art, especially in applications under high temperature conditions in the metallurgical industry, and has significant advantages. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is a schematic structural diagram of the overall assembly of MgAl2O4-V2AlC composite ceramic blades for use in the metallurgical industry of the present invention.

[0019] Figure 2 It is a side schematic diagram of a single MgAl2O4-V2AlC composite ceramic blade for use in the metallurgical industry according to the present invention.

[0020] Figure 3 It is a schematic structural diagram of a single MgAl2O4-V2AlC composite ceramic blade for metallurgical industry from another side angle of view of the present invention.

[0021] Figure 4 It is a front view of a single MgAl2O4-V2AlC composite ceramic blade for use in the metallurgical industry according to the present invention. DETAILED DESCRIPTION

[0022] The present invention will be further explained below in conjunction with the accompanying drawings and embodiments.

[0023] To avoid repetition, if not specifically mentioned, in this specific embodiment: MgAl2O4 powder purity ≥ 95wt%, particle size less than 3mm; V2AlC powder purity ≥ 95wt%, particle size less than 200μm; magnesium chromium spinel powder purity ≥ 95wt%, particle size less than 50μm; Si powder purity ≥ 95wt%, particle size less than 10μm; argon purity ≥ 99%. No further description is given in the embodiments.

[0024] To avoid repetition, the following methods are used to test the performance parameters of composite ceramic blades without special mention: The porosity is tested according to GB / T25995-2010 “Test method for density and apparent porosity of fine ceramics”.

[0025] The flexural strength was tested according to GB / T4741-1999 “Test method for flexural strength of ceramic materials”.

[0026] Refer to GB / T16535-1996 "Test Method for Linear Thermal Expansion Coefficient of Engineering Ceramics" to test the thermal expansion coefficient. The test temperature range is set according to the following experiment.

[0027] Referring to GB / T16536-1996 "Test method for thermal shock resistance of engineering ceramics", the number of thermal shock fractures was tested. The test temperature range was set according to the following experiment, and the water cooling was 15°C. Example

[0028] 80wt% MgAl2O4 powder and 20wt% V2AlC powder were weighed as raw materials and mixed evenly. First, 2wt% of the conditioning agent was added to the powder, and the conditioning agent consisted of magnesium chromium spinel, Si and polyethylene glycol in a mass ratio of 1:1:5. After mixing evenly, the mixture was molded at a pressure of 100MPa, maintained at pressure for 10min, and dried to obtain a green body.

[0029] The green body material was placed in a hot isostatic pressing sintering furnace and kept at 500°C in vacuum for 5 hours. Then, the temperature was raised to 1000°C in an argon atmosphere and kept at 100 MPa hot isostatic pressing for 10 hours to obtain a sintered green body, which was then machined on a CNC lathe to obtain a MgAl2O4-V2AlC composite ceramic blade.

[0030] The porosity is 3.02%, the flexural strength is 150.3MPa, the thermal expansion coefficient α is 1.1×10-6 / ℃ (room temperature ~ 1000℃), and the number of thermal shock fractures is 250 times (1100℃ ~ room temperature water cooling). Example

[0031] 85wt% of MgAl2O4 powder and 15wt% of V2AlC powder were weighed as raw materials, 2wt% of the tempering agent was added to the powder, and the mixture was evenly mixed and then compression molded. The compression molding pressure was 200MPa, and the pressure was maintained for 20min. After drying, a green body was obtained.

[0032] The green body material was placed in a hot isostatic pressing sintering furnace and kept at 700°C for 7 hours under vacuum conditions. Then, the temperature was raised to 1200°C in an argon atmosphere and kept at 150 MPa hot isostatic pressing conditions for 15 hours to obtain a sintered green body, which was then machined on a CNC lathe to obtain a MgAl2O4-V2AlC composite ceramic blade.

[0033] The porosity is 2.65%, the flexural strength is 175.8MPa, the thermal expansion coefficient α is 1.05×10-6 / ℃ (room temperature ~ 1000℃), and the number of thermal shock fractures is 280 times (1100℃ ~ room temperature water cooling).

[0034] Compared with Example 1, by increasing the proportion of MgAl2O4 powder and reducing the proportion of V2AlC powder, Example 2 exhibits better flexural strength and thermal shock resistance, but the porosity is slightly reduced. This shows that the reasonable adjustment of the ratio of MgAl2O4 to V2AlC can improve the mechanical strength of the material while maintaining high temperature performance, and is suitable for occasions with high requirements for impact resistance. However, it is still key to properly control the ratio of the two to balance the processing performance and high temperature impact resistance.

[0035] Example 3 Weigh 90wt% of MgAl2O4 powder and 10wt% of V2AlC powder, add 3wt% of the powder mass of the tempering agent, adopt the same mixing and compression molding process, the compression molding pressure is 300MPa, the pressure is maintained for 30min, and the green body is obtained after drying.

[0036] The green body material was placed in a hot isostatic pressing sintering furnace and kept at 800°C for 9 hours under vacuum conditions. Then, the temperature was raised to 1100°C in an argon atmosphere and kept at 150 MPa hot isostatic pressing conditions for 18 hours to obtain a sintered green body, which was finally machined into ceramic blades using a CNC lathe.

[0037] The porosity is 3.15%, the flexural strength is 160.4MPa, the thermal expansion coefficient α is 1.08×10-6 / ℃ (room temperature ~ 1000℃), and the number of thermal shock fractures is 230 times (1100℃ ~ room temperature water cooling).

[0038] Compared with Examples 1 and 2, Example 3 has a slightly higher ratio of the tempering agent and an increased sintering temperature, but due to the lower V2AlC content, the material is slightly inferior to the Examples with higher V2AlC content in terms of flexural strength and thermal shock resistance. However, during the processing, the higher compression molding pressure improves the compactness of the green body to a certain extent, further enhancing the mechanical strength of the material.

[0039] Example 4 Weigh 82wt% of MgAl2O4 powder and 18wt% of V2AlC powder, add 2wt% of the powder mass of the conditioning agent, the conditioning agent is composed of 1:1:5 mass ratio of magnesium chromium spinel, Si and polyethylene glycol. After mixing evenly, mold the mixture, the pressure of the molding is 250MPa, the pressure is maintained for 25min, and the green body is obtained after drying.

[0040] The green body material was placed in a hot isostatic pressing sintering furnace and kept at 700°C for 7 hours under vacuum conditions. Then, in an argon atmosphere, the temperature was raised to 1250°C and kept at 150 MPa hot isostatic pressing conditions for 15 hours to obtain a sintered green body, which was then processed into ceramic blades using a CNC lathe.

[0041] The test results show that the porosity is 2.85%, the flexural strength is 175.6MPa, the thermal expansion coefficient α is 1.07×10-6 / ℃ (room temperature ~ 1000℃), and the number of thermal shock fractures is 290 times (1100℃ ~ room temperature water cooling).

[0042] The flexural strength and thermal shock resistance of the material are enhanced by increasing the proportion of V2AlC and raising the hot isostatic pressing sintering temperature. Although the increase in the proportion of V2AlC increases the porosity of the material, the mechanical and thermal properties of the material are significantly improved, making it suitable for applications with high requirements for thermal shock resistance. Example

[0043] 88wt% of MgAl2O4 powder and 12wt% of V2AlC powder were weighed, and a conditioning agent of 5wt% of the powder mass was added, wherein the conditioning agent consisted of magnesium chromium spinel, Si and polyethylene glycol in a mass ratio of 1:1:5. After being mixed evenly, compression molding was performed, and the compression molding pressure was 280MPa, and the pressure was maintained for 30min, and a green body was obtained after drying.

[0044] The green body material was placed in a hot isostatic pressing sintering furnace and kept at 800°C for 9 hours under vacuum conditions. Then, the temperature was raised to 1200°C in an argon atmosphere and kept at 150 MPa hot isostatic pressing conditions for 18 hours to obtain a sintered green body, which was finally processed into a ceramic blade using a CNC lathe.

[0045] The test results show that the porosity is 2.95%, the flexural strength is 165.7MPa, the thermal expansion coefficient α is 1.08×10-6 / ℃ (room temperature ~ 1000℃), and the number of thermal shock fractures is 275 times (1100℃ ~ room temperature water cooling).

[0046] Example 5 sacrifices a certain amount of flexural strength (decreased compared to Example 4) by reducing the proportion of V2AlC, but the porosity of the material is good and the thermal expansion coefficient is kept low. In a high temperature environment, the material still exhibits good thermal shock resistance. Therefore, it is suitable for use in an application environment that does not require extremely high strength but requires excellent thermal expansion resistance.

[0047] In summary, the increase in V2AlC content can effectively improve the flexural strength and thermal shock resistance of ceramic materials. As the proportion of V2AlC increases, the number of thermal shock fractures gradually increases, and the material performs better under high temperature conditions. However, too high a V2AlC content will lead to an increase in porosity, which will have a certain impact on the mechanical strength of the material. Therefore, it is necessary to reasonably adjust the ratio of V2AlC to MgAl2O4 to ensure that while meeting the thermal shock resistance, it also maintains good mechanical strength and processing performance. The formulation of the tempering agent and the adjustment of the sintering process parameters (such as molding pressure, holding time, etc.) also play an important role in the material performance. By reasonably controlling these process parameters, the comprehensive performance of the material can be further optimized.

[0048] Comparative Example 1 80wt% of MgAl2O4 powder and 20wt% of V2AlC powder were weighed without adding a tempering agent, and then directly mixed and molded. The molding pressure was 100MPa, and the pressure was maintained for 10min. After drying, a green body was obtained.

[0049] The green body material was placed in a hot isostatic pressing sintering furnace and kept at 500°C for 5 hours under vacuum conditions. Then, the temperature was raised to 1000°C in an argon atmosphere and kept at 100 MPa hot isostatic pressing conditions for 10 hours to obtain a sintered green body, which was finally processed into ceramic blades using a CNC lathe.

[0050] The test results show that the porosity is 9.25%, the flexural strength is 97.3MPa, the thermal expansion coefficient α is 1.25×10-6 / ℃ (room temperature ~ 1000℃), and the number of thermal shock fractures is 170 times (1100℃ ~ room temperature water cooling).

[0051] Comparative Example 1 shows that failure to use a conditioning agent results in increased porosity and reduced flexural strength and thermal shock resistance.

[0052] 85wt% of MgAl2O4 powder and 15wt% of V2AlC powder were weighed, mixed directly without using a tempering agent, and then compression molded. The compression molding pressure was 200MPa, the pressure was maintained for 20min, and a green body was obtained after drying.

[0053] The green body material was placed in a hot isostatic pressing sintering furnace and kept at 700°C for 7 hours under vacuum conditions. Then, in an argon atmosphere, the temperature was raised to 1200°C and kept at 150 MPa hot isostatic pressing conditions for 15 hours to obtain a sintered green body, which was finally processed into ceramic blades using a CNC lathe.

[0054] The test results show that the porosity is 13.12%, the flexural strength is 91.8MPa, the thermal expansion coefficient α is 1.3×10-6 / ℃ (room temperature ~ 1000℃), and the number of thermal shock fractures is 165 times (1100℃ ~ room temperature water cooling).

[0055] It can be seen that not using tempering agent leads to the deterioration of material properties, especially the significant decrease in flexural strength and thermal shock resistance.

[0056] Comparative Example 3 The difference between Comparative Example 3 and Example 3 is that only the conditioning agent is set as follows, and other conditions remain unchanged: (1) A mixture of MgCr spinel, Si and polyethylene glycol in a ratio of 1:1:4; After testing, the porosity is 4.15%, the flexural strength is 135.6MPa, the thermal expansion coefficient α is 1.15×10-6 / ℃ (room temperature ~ 1000℃), and the number of thermal shock fractures is 220 times (1100℃ ~ room temperature water cooling). Different ratios of the tempering agent lead to a decrease in flexural strength and thermal shock performance.

[0057] (2) a mixture of 1:1:6 magnesium chromium spinel, Si and polyethylene glycol; After testing, the porosity is 4.20%, the flexural strength is 130.8MPa, the thermal expansion coefficient α is 1.17×10-6 / ℃ (room temperature ~ 1000℃), and the number of thermal shock fractures is 210 times (1100℃ ~ room temperature water cooling). Excessive addition of polyethylene glycol leads to a further decrease in flexural strength and affects thermal shock performance.

[0058] (3) 1:1 magnesium chromium spinel and Si; After testing, the porosity is 5.02%, the flexural strength is 120.4MPa, the thermal expansion coefficient α is 1.22×10-6 / ℃ (room temperature ~ 1000℃), and the number of thermal shock fractures is 180 times (1100℃ ~ room temperature water cooling). The lack of polyethylene glycol has a significant impact on the thermal shock performance and the mechanical strength of the material is also reduced.

[0059] (4) 1:5 Si and polyethylene glycol; After testing, the porosity is 5.56%, the flexural strength is 115.6MPa, the thermal expansion coefficient α is 1.25×10-6 / ℃ (room temperature ~ 1000℃), and the number of thermal shock fractures is 190 times (1100℃ ~ room temperature water cooling). Without adding magnesium chromium spinel, the porosity increases significantly, and the flexural strength and thermal shock performance decrease significantly.

[0060] In summary, the ratio of the conditioning agent has a significant effect on the porosity, flexural strength and thermal shock resistance of the material. The conditioning agent of magnesium chromium spinel, Si and polyethylene glycol in a mass ratio of 1:1:5 used in the present invention has the best comprehensive performance.

[0061] MgAl2O4 ceramics have a low thermal expansion coefficient close to zero, and have excellent corrosion resistance, high temperature resistance and high hardness. Magnesium aluminum spinel, as the only binary compound in the MgAl2O4-V2AlC system, has a high melting point, low thermal expansion coefficient, low thermal conductivity, stable chemical properties and excellent thermal shock resistance. At the same time, V2AlC not only has the high yield strength, high melting point and high thermal stability of ceramics, but also has good antioxidant properties. In addition, V2AlC's cubic isotropy, high hardness and high strength characteristics are highly favored in the fields of national defense, military, aerospace, medical equipment, etc.

[0062] Therefore, based on the characteristics of the two materials, the MgAl2O4-V2AlC composite ceramic blade of the present invention constructs a high-strength and high-toughness V2AlC bonding phase network in the MgAl2O4 material with a low thermal expansion coefficient, thereby improving the material's density, high-temperature strength, thermal vibration stability and wear resistance, thereby extending the service life of the ceramic blade. Specifically, the MgAl2O4-V2AlC composite ceramic blade has the following characteristics: (1) Different from traditional / oxide-carbide composite materials, due to the self-lubrication and high toughness of V2AlC metal ceramics, adding an appropriate amount of V2AlC enables the interface of the MgAl2O4-V2AlC material to form a continuous chemical bond under high temperature and high pressure, so that the MgAl2O4 composite material has high strength and high fracture toughness; (2) By introducing a tempering agent composed of a mixture of magnesium chromium spinel, Si and polyethylene glycol, the bonding and high-temperature stability of the composite material can be improved; (3) The cubic isotropy of V2AlC enables the CNC lathe to have good machining performance and precise size, and the composite ceramic blade has low damage, few defects and high yield.

[0063] The present invention combines the near-zero thermal expansion coefficient, low thermal conductivity, high melting point, thermal shock resistance, excellent thermal shock resistance of MgAl2O4 and the high bending strength, self-lubricity, wear resistance and certain damage tolerance of V2AlC. The MgAl2O4-V2AlC composite ceramic blade of the present invention constructs a high-strength and high-toughness V2AlC bonding phase network in the MgAl2O4 material with a low thermal expansion coefficient, improves the material's density, high-temperature strength, thermal vibration stability, wear resistance, high-temperature stability, and CNC lathe machining performance, and the composite ceramic blade has low damage, few defects, and a high yield, thereby extending the service life of the ceramic blade.

[0064] Reference Figure 1-Figure 4 As shown, the ceramic blades (1) are in a spiral fan-shaped structure, the spiral angle of the ceramic blades (1) is 15-25°, and the ceramic blades (1) are fixedly connected by welding plates (2), so that a spiral columnar structure is formed between the ceramic blades (1). The ceramic blades adopt a spiral fan-shaped structure, the spiral angle is 15-25°, and are fixedly connected by welding plates to form a spiral columnar structure, which significantly improves its working efficiency and stability under high temperature and high pressure environments. The spiral structure makes the flow of gas or liquid smoother, reduces turbulence and resistance, further optimizes the heat transfer and mass transfer effects, and improves the overall performance of the equipment. In addition, the structure further enhances the mechanical strength and durability of the blades, further reduces the risk of wear and damage of the blades under extreme working conditions, prolongs the service life, and improves reliability and service efficiency.

[0065] The foregoing is merely a specific embodiment of the present invention, which enables those skilled in the art to understand or implement the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features of the invention described herein.

Claims

1. A method for preparing MgAl2O4-V2AlC composite ceramic blades for metallurgical industry, characterized in that: The method comprises the following preparation steps: Step 1, raw material composition: 75-90wt% MgAl2O4 powder and 25-10wt% V2AlC powder are used as raw materials, and 2-10wt% of a conditioning agent is used as an additive; wherein the conditioning agent is a mixture of magnesium chromium spinel, Si and polyethylene glycol in a mass ratio of 1:1:5; Step 2, raw material mixing: the raw materials and additives in step (1) are configured in a percentage ratio, firstly, half of the conditioning agent is added to the MgAl2O4 powder and mixed, and the conditioning agent is covered on the surface of the MgAl2O4 raw material; after mixing evenly, V2AlC powder and the remaining conditioning agent are added in sequence, and mixed thoroughly, so that the V2AlC powder can cover the MgAl2O4 powder; Step 3, molding, sintering and processing: the raw materials mixed uniformly in step (2) are molded and dried to obtain a green body; the green body material is placed in a hot isostatic pressing sintering furnace, and kept warm at 500-900°C under vacuum conditions for 0.5-10 hours, and then the temperature is raised to 1000-1300°C in an argon atmosphere, and kept warm at 10-200 MPa hot isostatic pressing conditions for 2-20 hours to obtain a sintered green body, which is then machined on a CNC lathe to obtain a ceramic blade.

2. The method for preparing MgAl2O4-V2AlC composite ceramic blades for metallurgical industry according to claim 1, characterized in that: The MgAl2O4 powder has a purity of ≥95wt% and a particle size of less than 3mm.

3. The method for preparing MgAl2O4-V2AlC composite ceramic blades for metallurgical industry according to claim 1, characterized in that: The purity of the V2AlC powder is ≥95wt% and the particle size is less than 200μm.

4. The method for preparing MgAl2O4-V2AlC composite ceramic blades for metallurgical industry according to claim 1, characterized in that: The purity of the magnesium-chromium spinel powder is ≥95wt% and the particle size is less than 50μm.

5. The method for preparing MgAl2O4-V2AlC composite ceramic blades for metallurgical industry according to claim 1, characterized in that: The Si powder has a purity of ≥95wt% and a particle size of less than 10μm.

6. The method for preparing MgAl2O4-V2AlC composite ceramic blades for metallurgical industry according to claim 1, characterized in that: The molding pressure is 50-300 MPa, and the pressure is maintained for 5-30 minutes.

7. The method for preparing MgAl2O4-V2AlC composite ceramic blades for metallurgical industry according to claim 1, characterized in that: Argon purity ≥99%.

8. A MgAl2O4-V2AlC composite ceramic blade for metallurgical industry, characterized in that: The ceramic blades (1) are in a spiral fan-shaped structure, the spiral pitch angle of the ceramic blades (1) is 15-25 degrees, the ceramic blades (1) are fixedly connected by welding plates (2), and a spiral columnar structure is formed between the ceramic blades (1).

Citation Information

Patent Citations

  • Bending-resistant ceramic matrix composite material and powder metallurgy preparation method thereof

    CN105777132A